Advances in nanotechnology and its applications - Al-Khatib, Ma'an Fahmi Rashid (s.n, 2012)
Nanotechnology has emerged as one of the very promising technologies that will change the way things have been done before. The research in nanotechnology advanced speedily with the focus on creating new devices and materials that will be applied in various field. This book will present the enhancement of the characteristics of some existing materials and processes accomplished by introducing nano-materials